The effects of low-dose radiotherapy on fresh osteochondral allografts: An experimental study in rabbits - Uğur Gönç; Mehmet Çetinkaya; Mesut Atabek (Acta Orthopaedica et Traumatologica Turcica, 2016)
Objective: The aim of this study was to investigate the effects of low-dose fractionated radiotherapy on cartilage degeneration after distal femoral fresh massive osteochondral allograft transplantation. Methods: Twenty-four New Zealand White rabbits were divided into three groups of 8 rabbits each. All rabbits underwent distal femoral medial condyle fresh massive osteochondral allograft transplantation from California rabbits. The group 1 underwent transplantation without any preliminary process. The group 2 underwent fractionated local radiotherapy of 100 cGy for five days starting on the transplantation day. The group 3 included the rabbits to which the grafts transplanted after radiating in vitro by a single dose radiation of 1500 cGy. The hosts were sacrificed twelve weeks later. Anteroposterior and lateral radiographs were taken. Synovial tissue, cartilaginous tissue, and subchondral bone were assessed histopathologically. Results: Nonunion was present in three cases of group 2 and one of group 3 in which cartilage degeneration was more severe. Synovial hypertrophy and pannus formation were more obvious in non-radiated rabbits. Hypocellularity and necrosis of the subchondral bone were rare in group 2. More cartilage tissue impairment was present in group 3 compared to group 1. Conclusion: In osteochondral massive allograft transplantations, the immune reaction of the host could be precluded with radiotherapy, and the side-effects can be prevented by low-dose fractionated regimen. The total dose of fractionated radiotherapy for an immune suppression should be adjusted not to damage the cartilage tissue, but to avoid articular degeneration in the long term. Keywords: Osteochondral allograft, Radiotherapy, Cartilage degeneration, Animal study